Komparasi Efek Gasoline-Butanol dan Gasoline-Ethanol Terhadap Exhaust Gas Temperature dan Emissions Mesin EFI - Sanjaya, Firman Lukman; Fatkhurrozak, Faqih; Syarifudin, Syarifudin; Usaman , M. Khumaidi; Wibowo, Agus (P3M Politeknik Negeri Cilacap, 2024)
The use of gasoline in vehicles produces CO, HC, and NOx emissions which are dangerous for the environment. Using butanol and ethanol as additional gasoline can reduce pollutant emissions. This is because alcohol has a high oxygen content and helps combustion more completely. This research compares the Exhaust Gas Temperature and Emissions results of EFI engines using gasoline-butanol and gasoline-ethanol. The EFI engine used has a capacity of 150CC. The alcohol used was butanol and ethanol with a percentage of 5%, 10%, and 15% in each test. The test results showed that the highest EGT reduction occurred in the E15 mixture at 23.98% and B15% at 8.65. Meanwhile, CO emissions experienced the highest reduction in E10 by 53.6% and B15 by 44.6%. HC emissions also experienced the highest reduction in E15 by 70.5% and B15 by 66.7% compared to gasoline. However, CO2 emissions increased to 17.07% in the E15 mixture and 11.46% in B15. This proves that the addition of ethanol produces more complete combustion than the addition of butanol.